Comparative Effectiveness and Safety of Milrinone and Levosimendan as Initial Inotrope Therapy in Patients With Acute Heart Failure With Renal Dysfunction. Issue 6 (June 2022) - Cui, Xueyan; Wang, Zhongsu; Dong, Xue; Cheng, Zijie; Zhang, Le; Mu, Yan; Huang, Xin; Li, Yan; Hong, Yinglong; Han, Yi
Abstract : Supplemental Digital Content is Available in the Text. Abstract: Levosimendan and milrinone are 2 effective inotropic drugs used to maintain cardiac output in acute heart failure (AHF). Using data from patients with AHF with and without abnormal renal function, we performed this single-center, retrospective cohort study to compare the effectiveness and safety of milrinone and levosimendan for the initial management of AHF. Patients admitted for heart failure between December 2016 and September 2019 who received levosimendan or milrinone as initial inotrope therapy in the cardiology department were identified. A total of 436 levosimendan and 417 milrinone patients with creatinine clearance (CrCl) ≥30 mL/min and 50 levosimendan and 71 milrinone patients with CrCl <30 mL/min or on dialysis were included. The primary outcome was a composite of changes in clinical status at 15 and 30 days after initial inotrope therapy discontinuation. Between subgroups of patients with CrCl ≥30 mL/min, there were no significant differences in primary outcomes; milrinone was associated with more frequent hypotension and cardiac arrhythmias during the infusion period ( P < 0.01), while levosimendan was associated with more frequent cardiac arrhythmias within 48 hours after discontinuation ( P < 0.05). Of the patients with CrCl <30 mL/min or on dialysis, more initial levosimendan than milrinone patients and those who switched to alternative inotropes experienced clinical worsening at 15 days and 30 days ( P < 0.05). According to our results, patients with AHF with severe renal dysfunction should avoid initial inotrope therapy with levosimendan.